The Clinical Features of Binge Eating Disorder and Bulimia Nervosa: What are the differences? - Sullivan, Keri A. (Canadian Journal of Counselling and Psychotherapy, 2007)
This study compared the clinical characteristics of binge eating disorder (BED) and the related syndrome bulimia nervosa (BN) in a community sample of women. Diagnostic assessment was established by using the Eating Disorder Examination (EDE) interview. Findings suggest individuals with BED are distinguishable from those with BN on a number of traits, including higher rates of obesity and lower levels of eating concern and dietary restraint. Individuals with these different diagnoses share some important psychological and behavioural features, such as shape and weight concern. Findings are discussed in terms of the diagnostic utility of the BED category as well as treatment implications for the BED individual.